(untitled) (Third Sector Social Economic Review, 2025)
The Sustainable Development Goals (SDGs) determined by the United Nations are a global paradigm that brings together the goals of economic growth, social welfare and environmental protection. SDGs 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation and Infrastructure), representing the economic dimension of SDGs, foresee increasing the sustainability and inclusiveness of economic growth and supporting it with innovation-focused industrial policies and infrastructure investments. This study aims to evaluate Turkey’s performance in terms of SDG 8 and SDG 9 targets in the context of SDGs and to guide policy makers by providing a perspective for Turkey on its sustainable development journey within the scope of the findings obtained. The reason for focusing on SDG 8 and SDG 9 targets in particular within the scope of the research is the critical importance of these targets in terms of sustainable structural development due to their relationships with inclusive economic growth, employment, industrial and infrastructure investments. In this context, Turkey’s current situation was analyzed using Entropy and VIKOR methods on economic, social and environmental indicators by making comparisons with OECD member countries. The findings obtained as a result of the analysis conducted reveal that Turkey ranks second to last among the 28 OECD member countries included in the study, in the context of the criteria considered within the scope of the research.